2024
DOI: 10.3389/fchem.2024.1327113
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable biosurfactant production from secondary feedstock—recent advances, process optimization and perspectives

Yahui Miao,
Ming Ho To,
Muhammad Ahmar Siddiqui
et al.

Abstract: Biosurfactants have garnered increased attention lately due to their superiority of their properties over fossil-derived counterparts. While the cost of production remains a significant hurdle to surpass synthetic surfactants, biosurfactants have been anticipated to gain a larger market share in the coming decades. Among these, glycolipids, a type of low-molecular-weight biosurfactant, stand out for their efficacy in reducing surface and interfacial tension, which made them highly sought-after for various surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 206 publications
(213 reference statements)
0
7
0
Order By: Relevance
“…Enhanced sustainability of rhamnolipid and sophorolipid biosurfactant production has been attempted by employing second-generation feedstocks [ 59 , 60 , 61 , 62 ], specifically industrial residual biomass waste streams such as sunflower oil, waste fried oil, jatropha oil, and animal fat (as hydrophobic substrates), and sugarcane molasses, soy molasses, glycerol (as hydrophilic substrates), and food waste. In this scenario, municipal unsorted food waste (MBW) and its anaerobic digestates are the most sustainable waste materials to use as potential waste feedstock.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced sustainability of rhamnolipid and sophorolipid biosurfactant production has been attempted by employing second-generation feedstocks [ 59 , 60 , 61 , 62 ], specifically industrial residual biomass waste streams such as sunflower oil, waste fried oil, jatropha oil, and animal fat (as hydrophobic substrates), and sugarcane molasses, soy molasses, glycerol (as hydrophilic substrates), and food waste. In this scenario, municipal unsorted food waste (MBW) and its anaerobic digestates are the most sustainable waste materials to use as potential waste feedstock.…”
Section: Discussionmentioning
confidence: 99%
“…For the bacterial sophorolipids and rhamonlipids biosurfactants [ 6 ] representing model products to be matched for performance by the chemical surfactants according to scheme 2, the employed approaches to improve their productivity are the optimization of culture conditions, the selection of robust microorganisms, the genetic modification of microorganisms, and the development of novel cost-effective downstream processes [ 60 , 61 , 72 , 73 , 74 ]. In spite of the great amount of research, according to the authors of the present work, the major factor hindering the scale-up of the results obtained by previous workers to the industrial level is the application of processes based on biotechnology that do not allow a real, consistent breakthrough in the end product cost reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning bioprocess development, of which a detailed review is outside the scope of this manuscript, while the reported maximum productivities of SLs and RLs are 3.7 and 1.54 g/L/h, respectively, MELs' maximum productivities are significantly lower at values of 0.59 g/L/h [115]. In addition to lower productivity and consequent needs for CAPEX investment, other important cost-drivers are related to the use of pure substrates and the downstream process, which represents approximately 60% of the total production cost [3].…”
Section: Current and Future Perspectives On Mels In The Marketmentioning
confidence: 97%
“…Rhamnolipid, a glycolipid extensively studied, comprises of 2 molecules of fatty acids (β-hydroxydecanoic acid) and 2 molecules of rhamnose sugar. The genus Pseudomonas , which includes Pseudomonas aeruginosa and Pseudomonas cepacian , is the most prolific generator of Rhamnolipids, although other bacterial species including Serratia rubidaea and Lysinibacillus sphaericus can also create them ( Miao et al, 2024 ).…”
Section: Roles Of Microbial Communities In Prementioning
confidence: 99%